2011
DOI: 10.1038/ajh.2011.12
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 Supplementation for 16 Weeks Improves Flow-Mediated Dilation in Overweight African-American Adults

Abstract: Background A growing body of evidence has linked vitamin D deficiency to increased risk of cardiovascular disease. Vitamin D deficiency is also more common in African Americans for whom an increased cardiovascular disease risk exists. This study sought to test the hypothesis that 16 weeks of 60,000 IU monthly supplementation of oral vitamin D3 would improve flow-mediated dilation (FMD) in African Americans, whereas no change would be observed in the placebo group. Methods A randomized, double blind, placebo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(96 citation statements)
references
References 15 publications
5
90
1
Order By: Relevance
“…(31) Second, vitamin D 3 supplementation ($2000 IU/d) was found to improve endothelial function in a trial among African American individuals compared to placebo. (32) Third, mice lacking the vitamin D receptor (VDR) suffer from hypertension and develop heart hypertrophy. (33,34) Fourth, clinically, in two small trials among patients with mild hypertension and older postmenopausal women, ultraviolet B (UVB) irradiation or vitamin D supplementation (800 IU/d) reduced blood pressure by 6 to 9 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…(31) Second, vitamin D 3 supplementation ($2000 IU/d) was found to improve endothelial function in a trial among African American individuals compared to placebo. (32) Third, mice lacking the vitamin D receptor (VDR) suffer from hypertension and develop heart hypertrophy. (33,34) Fourth, clinically, in two small trials among patients with mild hypertension and older postmenopausal women, ultraviolet B (UVB) irradiation or vitamin D supplementation (800 IU/d) reduced blood pressure by 6 to 9 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…A couple of cross-sectional studies in healthy adults show lower serum levels of 25(OH)D to be associated with endothelial dysfunction (91,92) . A few trials show an improvement in flow-mediated dilation with vitamin D supplementation (93)(94)(95) , but most show no effect (79,(96)(97)(98) ( Table 2).…”
Section: Endothelial Functionmentioning
confidence: 99%
“…We have found no association between 25-OH D, PTH or body mass indices with fasting glycemia, HbA1c or duration of diabetes. Although epidemiological studies and meta-analysis showed an association between low serum 25-OH D and impaired glycaemia (Pittas et al, 2010;Mitri et al, 2011), vitamin D intervention trials have had inconsistent results (Avenell et al, 2009;Von Hurst et al, 2010;Harris et al, 2011;Davidson et al, 2013). Therefore, it is uncertain whether vitamin D deficiency and poor glycemic control are causally interrelated or they represent two independent features of T2DM.…”
Section: -Oh D Level and Glucose Metabolismmentioning
confidence: 99%